2009
DOI: 10.1002/cncr.24614
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic disparity in mortality after diagnosis of colorectal cancer among inner city minority New Yorkers

Abstract: Networked polymers that had poly(ethylene glycol) (PEG) chains and lithium sulfonylimide salt structures were prepared by curing a mixture of poly(ethylene glycol) diglycidyl ether and lithium 3‐glycidyloxypropanesulfonyl‐trifluoromethanesulfonylimide with poly(ethylene glycol) bis(3‐aminopropyl) terminated. The obtained flexible self‐standing networked polymer films showed high thermal and mechanical stability with relatively high ionic conductivity. The room temperature ionic conductivity under a dry conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Disparity in health care access has been identified in a variety of medical conditions. In adult medicine differences in access, treatment, and overall outcomes have been described among disease states such as heart disease, 8,12,18,24 cancer, 1,8,15,17,23 and diabetes. 25,27 Li et al 18 retrospectively reviewed data for 207,570 Medicare enrollees hospitalized for acute myocardial infarction in Pennsylvania be- 20 These authors found that across wide-ranging diseases, African American and ethnic minorities often lacked the same access to medical treatment and health services compared with Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Disparity in health care access has been identified in a variety of medical conditions. In adult medicine differences in access, treatment, and overall outcomes have been described among disease states such as heart disease, 8,12,18,24 cancer, 1,8,15,17,23 and diabetes. 25,27 Li et al 18 retrospectively reviewed data for 207,570 Medicare enrollees hospitalized for acute myocardial infarction in Pennsylvania be- 20 These authors found that across wide-ranging diseases, African American and ethnic minorities often lacked the same access to medical treatment and health services compared with Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic and socioeconomic disparities exist among patients with numerous diseases, such as colorectal and cervical cancer, cardiovascular disease, and diabetes 6–9. Various ethnic groups have been found to have less access to insurance coverage, preventive resources, and primary and specialty care 7.…”
Section: Introductionmentioning
confidence: 99%
“…Co-existing chronic illness is associated with a substantial reduction in life expectancy after diagnosis of early stage CRC and also affects the tolerance to various therapies [16,17]. A high proportion (9/14, 64%) of cancers was stage III or IV, which is higher than reported previously in AA and Hispanics [18]. This suggests that symptomatic patients are more likely to have advanced staging of CRC at diagnosis.…”
Section: Discussionmentioning
confidence: 93%